EFFECT OF ADDING WHEAT PEAT AND SPRAYING WITH ITS EXTRACT AND ORGANIC NUTRIENT VEGEAMINO ON GROWTH AND YIELD OF RED CABBAGE - & AL-Ubaidy, AL-Zaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was carried out at the field of Horticulture Dept. Fild – Coll. Agric, Baghdad University, to study the effect of wheat peat and spraying its extract and organic nutrient vegeamino on growth and yield of the red cabbage (Raissa Hybrid). during winter season of 2015-2016. factorial experiment using randomized complete block design with three replicaes, The first fatcor includes five levels of organic fertilizer, no-fertilizer (P0), recommended chemical fertilizer (100 N,120 P205 and 120 K2O kg . h -1( (P1), organic fertilizer 7.5 tan.h-1, organic fertilizer 15 tan.h-1 and organic fertilizer 30 tan.h -1. the second factor four treatments , spraying only weter (E0), extracts wheat peat (E1) at a concentration 2 ml.L-1, organic nutrient vegeamino (E2) at 1 ml.L-1 and Interaction E1 + E2 (E3). All levels of organic fertilizers showed a significant increase in vegetative and quantitative characteristics for the yield as plant height, number of external leaves, thickness of leafe necks, leaf area, head diameter, head weight, early yield and total yield compared with control (P0). P4 treatment gave greatest value of these characteristics which reached 28.31 cm,16.218 leaf. plant-1, 14.144 mm ,76.25 dcm2. Leaf -1, 18.76 cm, 1584 g, 10.500 tan.h-1, 40.654 tan.h-1 respectively. (E1) and (E2) treatments showed a significant increase in the above vegetative and quantitative characteristics compared with control (E0), treatment E3 gave greatest value which reached 27.92 cm,16.086 leaf. Plant -1, 13.721 mm,73.15 dcm2. Leaf -1, 18.34 cm 1535g, 8.444 tan.h-1, 39.405 tan.h-1 respectively, Interaction treatment of P4E3 gave greatest value which reached 29.51 cm ,18.107 leaf. Plant -1, 14.833 mm, 87.25 dcm2. Leaf -1, 20.22 cm, 1773 g , 12.748 tan.h-1, 45.507 tan. h-1 respectively.